Impact of Foreign Trade and Foreign Direct Investment on the Labour Market in Central and Eastern Europe. The Case of Poland - Wysokińska, Zofia; Witkowska, Janina (Comparative Economic Research. Central and Eastern Europe, 2006)
The aim of this chapter is to assess the activities of international business from the point of view of its effects on the labour market of Poland as a country in Central and Eastern Europe which was in the process of undergoing systemic transformation. This analysis covers two spheres, i.e. foreign trade and the activities of transnational corporations in Poland. An attempt will be made to discuss the following issues: Implications of the international business on the situation on the labour market of the economy undergoing the transformation from the centrally planned into market economy; Consequences of the establishment of the free trade area with the EU in Poland and the trade liberalization process within the WTO for the Polish labour market during the accession period; Implications of the inflow of foreign direct investment into Poland on the labour market situation.